2021
DOI: 10.29219/fnr.v65.3448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the antimicrobial peptide WK3 on diarrhea, growth performance and intestinal health of weaned piglets challenged with enterotoxigenic Escherichia coli K88

Abstract: Background: Antibiotics are very effective for treating diarrhea in weaned pigs, but the global prohibition of antibiotics makes it urgent to find an alternative to antibiotics. Objective: An experiment was conducted to determine the antimicrobial activity of a linear trpzip-like β-hairpin antimicrobial peptide WK3 in vivo and to assess its effects on growth performance and intestinal health. Design: Thirty-two piglets were weaned at 21 days and housed in individual metabolic cages, which were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…The fed piglets Ceprocin AD had also higher levels of secretory IgA in the jejunum and of serum IgA and IgG compared with the control. The results on pro-inflammatory factors IL-1β and IL-6 were not in accordance with the effect seen in other studies, where reductions in pro-inflammatory cytokines are generally reported [ 223 , 224 , 228 , 229 ].…”
Section: Strategies To Prevent/reduce Post-weaning Diarrhoeacontrasting
confidence: 82%
See 2 more Smart Citations
“…The fed piglets Ceprocin AD had also higher levels of secretory IgA in the jejunum and of serum IgA and IgG compared with the control. The results on pro-inflammatory factors IL-1β and IL-6 were not in accordance with the effect seen in other studies, where reductions in pro-inflammatory cytokines are generally reported [ 223 , 224 , 228 , 229 ].…”
Section: Strategies To Prevent/reduce Post-weaning Diarrhoeacontrasting
confidence: 82%
“…Unlike antibiotics, which target specific cellular activities (e.g., the synthesis of DNA, protein, or cell wall), AMPs target the lipopolysaccharide layer of cell membrane, which is ubiquitous in microorganisms [ 47 ]. Importantly, this makes it difficult for bacteria to develop resistance against these peptides, i.e., due to their ability to disrupt bacterial membranes via non-specific electrostatic interactions with the membrane lipid components [ 220 , 223 , 224 ]. Therefore, antimicrobial peptides may have potential as an alternative to antibiotics for use in livestock production.…”
Section: Strategies To Prevent/reduce Post-weaning Diarrhoeamentioning
confidence: 99%
See 1 more Smart Citation
“…This was also observed by previous studies, which found that adding compound AMPs in the diet improved the growth performance of piglets, thus increasing the effective utilization rate of feed and bringing more economic benefits to farmers ( 18 , 19 ). In addition, adding antimicrobial peptide WK3 in the diet attenuated diarrhea symptoms of ETEC K88 challenged pig models and improved growth performance of piglets ( 20 ). The results of this experiment are consistent with the results of the studies mentioned above, in which adding IAMPs in the diets of weaning piglets improved the growth performance and attenuated the diarrhea rate of piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous feed additives have already been proposed as potential alternatives to ZnO (6,20). Feed additives, which potentially reduce the incidence of PWD include for example organic acids (39)(40)(41), probiotics (42)(43)(44)(45), prebiotics (46, 47), essential oils and other plant based substances (48, 49), exogenous enzymes (50,51), dehydrated porcine plasma (52), yeast (53) and antimicrobial peptides (54,55). However, while most studies on alternative strategies to reduce the usage of antimicrobial substances focus on feed additives, only a few studies report on the impact of management, housing conditions and biosecurity (56).…”
Section: Introductionmentioning
confidence: 99%